Penguatan Karakter Baik Peserta Didik Melalui Kegiatan Budaya Mangupa Dalam Proses Pembelajaran Tutor di SAS English Laboratory - Abdul Marif; Syarifah Ainy Rambe; Husrin Konadi; Asnarni Lubis (LPPI UMN AL WASHLIYAH, 2025)
This community service program was conducted at SAS English Laboratory, a non-formal educational institution focused on English language instruction. The program involved 12 tutors who were actively engaged in teaching, yet had not integrated character development as an added value in their instructional process. Character strengthening—especially through emotional cultivation (olah rasa)—is essential for shaping learners with strong emotional and social resilience. To address this issue, the program was implemented through three main stages: socialization, application of science and technology (IPTEK), and training on designing character education rubrics. The training incorporated the cultural wisdom of Mangupa, which emphasizes mutual tolerance, respect, self-confidence, and effective communication as core values of good character. As a result, the tutors were able to develop and apply character assessment rubrics in their teaching practices. These rubrics serve as a tool to reduce the likelihood of students becoming victims of bullying, both in educational and social environments. In-depth interviews revealed that the tutors fully supported the implementation of character assessment, even within a non-formal educational context. This program demonstrates that character education rooted in local culture can be effectively integrated into English language teaching.